2012
DOI: 10.1111/j.1447-0594.2012.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Japanese “Prevention of Long‐term Care” project for the improvement in oral function in the high‐risk elderly

Abstract: The effects of intervention were clearly recognized in regards to oral diadochokinesis. Improvement in RSST and oral diadochokinesis scores was marked in those persons showing a lower number of articulations before intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 11 publications
1
68
1
Order By: Relevance
“…The Basic Checklist has been used to select participants in some of them, in addition to being adopted as an index to measure the outcomes of physical activity interventions . It has also been used to select participants by investigators who examine other types of intervention . The Basic Checklist is a useful instrument for multiple purposes, such as selecting care prevention program participants and measuring outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The Basic Checklist has been used to select participants in some of them, in addition to being adopted as an index to measure the outcomes of physical activity interventions . It has also been used to select participants by investigators who examine other types of intervention . The Basic Checklist is a useful instrument for multiple purposes, such as selecting care prevention program participants and measuring outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that performing tongue and pronunciation exercises promotes recovery of decreased motion function and improvement of eating and swallowing function. An earlier study of elderly individuals with extremely poor oral function who required nursing care 8) also found that implementation of an oral function training program for 3 months resulted in a marked improvement in the RSST score and rate of oral diadochokinesis. This indicates that swallowing exercises promote recovery of motion function in the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…For measuring oral diadochokinesis, the participants were asked to articulate the 'pa' syllable repetitively as quickly as possible for 5 s, and the number of articulations was counted 25 . The same procedure was repeated for syllables 'ta' and 'ka', and the number of articulations was counted using a digital counter (T.K.K.…”
Section: Assessment Of Oral Functionmentioning
confidence: 99%